Effect of self-interaction corrections (SIC) on physical properties of small Al, Ag and Ni nanoparticles - Leiro Jarkko (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The density functional method with self-interaction corrections (SIC) has been used to calculate the static dipole polarizations and surface plasmons of small metallic nanoparticles. It turns out that SIC lower the static dipole polarization per atom in the case of Al clusters when decreasing the number of atoms. In the case of silver, the dipole plasmon like excitation energies increase on going to smaller nanoparticles. The comparison with experiments has been shown to be in good agreement. Also, the static dipole polarizabilities of the Ni nanoparticles have been considered.